Research progress on gut microbiota-mediated early life influencing factors on childhood obesity - Xiaochuan WANG; Borui LIU; Ningyu WAN; Lu ZHENG; Zhe YANG; Jiajin HU; Deliang WEN (Editorial Office of Chinese Journal of Public Health, 2024)
The early stage of life is a critical period for the colonization and formation of the gut microbiota. Research has shown that the colonization and formation of the gut microbiota in the early stage of life is associated with the development of obesity in childhood. The colonization of the infant gut microbiota is highly influenced by early life factors such as mode of delivery, premature birth, exposure to antibiotics, and feeding methods. Understanding the early life influencing factors, changes in the infant gut microbiota, and the trajectory of childhood obesity development can help reveal the potential mechanisms underlying the association between early life factors and childhood obesity. It can also provide reference and guidance for finding intervention targets for childhood obesity and achieving early prevention and control of obesity. Therefore, this article provided a systematic overview of research on the association between gut microbiota-mediated early life influencing factors and childhood obesity.